Nonsyndromic supernumerary teeth in patients in National Taiwan University Children's hospital - Feng-Chou Cheng; Mu-Hsiung Chen; Bo-Lin Liu; Shu-Yu Liu; Yu-Ting Hu; Julia Yu-Fong Chang; Chun-Pin Chiang (Elsevier, 2022)
Background/purpose: A literature review reveals limited data for supernumerary teeth in Taiwan. This study aimed to analyze the characteristics of nonsyndromic supernumerary teeth in patients in the National Taiwan University Children's Hospital. Materials and methods: This retrospective study analyzed the nonsyndromic supernumerary teeth in 1280 patients (710 boys and 570 girls) based on examination of mainly panoramic radiographs and related radiographs. Chi-square test was used for trend analysis. Results: The incidence of nonsyndromic supernumerary teeth was 11.25% (179 supernumerary teeth in 144 of the 1280 patients). There was a male predominance (4.33: 1, P < 0.0001) for our 144 patients. Most supernumerary teeth were single (63.69%), conical-shaped (78.77%), and unerupted (77.09%). Supernumerary teeth also tended to be located in the premaxilla (93.85%), fully developed (51.40%), invertedly oriented (45.25%), sagittally located in a palatal/lingual position (67.60%), and adjacent to the root and root apex of permanent teeth (70.39%). The supernumerary teeth with a normal orientation (64.52%) had a high potential to erupt into the oral cavity, but the majority of the supernumerary teeth with a transverse orientation (97.22%) or an inverted orientation (100%) were unerupted. Conclusion: The nonsyndromic supernumerary teeth occur most commonly in male patients with a male to female ratio of 4.33: 1. The incidence of nonsyndromic supernumerary teeth in our 1280 patients is 11.25%, and the most frequent location of supernumerary teeth is the anterior maxillary region. More than three quarters of supernumerary teeth are conical-shaped or unerupted. Inverted supernumerary teeth are all embedded in the jawbones.